Discordance of Non-HDL and Directly Measured LDL Cholesterol: Which Lipid Measure is Preferred When Calculated LDL Is Inaccurate?. (23rd April 2013) - Baruch, Lawrence; Chiong, Valerie J.; Agarwal, Sanjay; Gupta, Bhanu
Abstract : Objective . To determine if non-HDL cholesterol (N-HDL) and directly measured LDL cholesterol (D-LDL) are clinically equivalent measurements. Patients and Methods . Eighty-one subjects recruited for 2 cholesterol treatment studies had at least 1 complete fasting lipid panel and D-LDL performed simultaneously; 64 had a second assessment after 4 to 6 weeks, resulting in 145 triads of C-LDL, D-LDL, and N-HDL. To directly compare N-HDL to D-LDL and C-LDL, we normalized the N-HDL by subtracting 30 from the N-HDL (N-HDLA ). Results . There was significant correlation between N-HDLA, D-LDL, and C-LDL. Correlation was significantly greater between N-HDLA and C-LDL than between N-HDLA and D-LDL. A greater than 20 mg/dL difference between measures was observed more commonly between N-HDLA and D-LDL, 29%, than between C-LDL and N-HDLA, 11% (P < 0.001 ), and C-LDL and D-LDL, 17% (P = 0.028 ). Clinical discordance was most common, and concordance was least common between N-HDL and D-LDL. Conclusions . Our findings suggest that N-HDL cholesterol and D-LDL cholesterol are not clinically equivalent and frequently discordant. As N-HDL may be superior to even C-LDL for predicting events in statin-treated patients, utilizing N-HDL to guide therapy would appear to be preferable to D-LDL when C-LDL is inaccurate.